2010
DOI: 10.4236/msa.2010.14035
|View full text |Cite
|
Sign up to set email alerts
|

Molar Binding Energy of Zigzag and Armchair Single-Walled Boron Nitride Nanotubes

Abstract: Molar binding energy of the boron nitride single-walled zigzag and armchair nanotubes is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…In particular, quasi-classical approach can be used for this purpose (physical theory and related mathematical problems see in [33] and [34,35], respectively), which successfully have been applied to other structural modifications of boron nitride. Recently, the relative stability of the small-and intermediate-diameter BN nanotubes has been studied by this method, and a complex dependence of the molar energy on the diameter was obtained [30,36]. As for the equilibrium bonds length, for all calculated single-walled boron nitride nanotubes it is found to be in satisfactory agreement with experimental value obtained for the intra-layer bonds length in BN layered crystals.…”
Section: Analytical Polyhedral Modelsupporting
confidence: 63%
“…In particular, quasi-classical approach can be used for this purpose (physical theory and related mathematical problems see in [33] and [34,35], respectively), which successfully have been applied to other structural modifications of boron nitride. Recently, the relative stability of the small-and intermediate-diameter BN nanotubes has been studied by this method, and a complex dependence of the molar energy on the diameter was obtained [30,36]. As for the equilibrium bonds length, for all calculated single-walled boron nitride nanotubes it is found to be in satisfactory agreement with experimental value obtained for the intra-layer bonds length in BN layered crystals.…”
Section: Analytical Polyhedral Modelsupporting
confidence: 63%
“…Recent studies have demonstrated that graphene, transition metal dichalcogenides, and other twodimensional (2D) layered materials have great potential for the development of future advanced material systems and nanodevices. [1][2][3][4][5][6] Hexagonal boron nitride (h-BN) is one such 2D material that has stimulated extensive interest both theoretically [7][8][9][10][11] and experimentally. 3,12,13 This insulating, wide bandgap ($ 6 eV) material is sometimes referred to as \white graphene" due to its white appearance in powder form andits hexagonal lattice structure.…”
Section: Introductionmentioning
confidence: 99%
“…A semi-empirical estimate of the ratio of the bond strengths of boronitrene/graphene, taking into account the bond length and the effectively bonded valence electron number, yields a value of 0.71 for the tensile unbinding forces and 0.72 for the tensile bond strengths [49]. A somewhat higher ratio of the bonding energies of 0.75 is obtained from the dissociation energies determined by MD simulations for the sp 2 -hybridized B-N bond of 4.0 eV [50,51] in comparison with 5.37 eV for the sp 2 -hybridized carbon bond [52]. Furthermore, the ratio of the lowest line energies with reconstructed edges of boronitrene and graphene is with 0.80 still in reasonable agreement with the ratio of bond strengths and bond energies.…”
Section: Intrinsic Boronitrenementioning
confidence: 97%
“…In figure 3 the boronitrene/graphene ratios of the Young's modulus, fracture strength, line energy, and fracture toughness are compared with the ratio of the ideal tensile strengths obtained by the bond force model [49] and the chemical bond energies [50][51][52]. This plot suggests that the differences in the mechanical properties of boronitrene and graphene, not only of their fracture strength, can be explained by the different bond strength and dissociation energy of the constituent bonds.…”
Section: Intrinsic Boronitrenementioning
confidence: 99%